Results-Based Approaches in Development : A Review - World Bank (World Bank, Washington, DC, 2016)
After falling out of fashion somewhat (Schmitz, 2006) there has been a resurgence of interest in conditional or results-based instruments over the last few years. Faced with increasing pressure on budgets and sometimes frustrated with the perceived ineffectiveness of development spending, policy makers have started to explore new ways of structuring development support in order to do more with less. However, as is well known, conditionality has a mixed track record. It is therefore important to understand where, when, and how these new instruments are best deployed; what their strengths are, and what their weaknesses; and what critical information we are still missing about them. Initial research on these new instruments is emerging, but so far there is no overarching structure or overall research program that unifies these efforts. A review that provides a general overview of this burgeoning field may therefore be useful both to policy makers and to researchers: it can both summarize the current state of the art and it may help to prevent duplicate research as well as identify gaps that could usefully be filled. This paper conducts such a review and seeks to summarize the already existing research on this topic. The report is structured as follows. First the authors give an overview of the subject matter, describing the concept and the terminology of results-based approaches. Next, they survey the research landscape on this topic, pointing out which areas are well covered, and which ones less so. In sections four and five the authors then structure and summarize the start of the art in theoretical research (section four) and in empirical research (section five). The authors conclude with some overarching findings and questions for further research.